2007
DOI: 10.1002/mds.21340
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε4 allele is associated with Parkinson disease risk in a Mexican Mestizo population

Abstract: We investigated the association between apolipoprotein E (APOE) alleles and genotypes and Parkinson disease (PD) in 229 unrelated Mexican Mestizo PD patients and 229 controls. Results showed that both APOE-epsilon4 allele and APOE epsilon4/epsilon3 genotype are associated with PD (OR = 1.736, P = 0.011; OR = 1.688, P = 0.019, respectively). Mean age at onset of PD was not associated to any APOE allele or genotype, but was significantly earlier in familial PD when compared to sporadic cases (P = 0.025).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
16
0
2
Order By: Relevance
“…While some studies showed that the presence of APOE -ε4 or APOE -ε2 increases the risk of PD (Huang et al, 2004; Lopez et al, 2007; Pulkes et al, 2011), others showed either a negative or no relationship between apoE genotypes and PD (Gao et al, 2011; Kurz et al, 2009; Williams-Gray et al, 2009). Notably, a large study with 3,465 case and control samples from the NINDS Neurogenetics repository revealed no association between apoE and PD (Federoff et al, 2012).…”
Section: Genetic Clinical and Experimental Evidence For Protective Ementioning
confidence: 99%
“…While some studies showed that the presence of APOE -ε4 or APOE -ε2 increases the risk of PD (Huang et al, 2004; Lopez et al, 2007; Pulkes et al, 2011), others showed either a negative or no relationship between apoE genotypes and PD (Gao et al, 2011; Kurz et al, 2009; Williams-Gray et al, 2009). Notably, a large study with 3,465 case and control samples from the NINDS Neurogenetics repository revealed no association between apoE and PD (Federoff et al, 2012).…”
Section: Genetic Clinical and Experimental Evidence For Protective Ementioning
confidence: 99%
“…Previous work has suggested ε4 as a risk factor for the age of onset, decline in cognitive impairment, and/or development of dementia in PD, ε2 has also been identified as a potential risk factor in PD, however this is at best a weak effect, and inconsistent across studies (Buchanan et al, 2007; Ezquerra et al, 2008; Gallegos-Arreola et al, 2009; Huang et al, 2006; Huang et al, 2004; Kurz et al, 2009; Lopez et al, 2007; Martinez et al, 2005; Pankratz et al, 2006; Ryu and Kwon, 2010; Vefring et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In the current work, we report the initial results of a multidisciplinary effort aimed to the analysis of multiple genetic risk factors for PD in a case control sample in Colombia, a South American population; being the first systematic study of several common genetic markers for PD in Latin America. A previous paper reported an association with a single polymorphism in APOE gene in a PD sample from Mexico (López et al 2007). Mean life expectancy for Colombia was 72.3 years in 2005 (Forero et al 2006b).…”
Section: Discussionmentioning
confidence: 97%